2020
DOI: 10.1108/bfj-08-2019-0651
|View full text |Cite
|
Sign up to set email alerts
|

Economic sustainability of wine tourism services and direct sales performance – emergent profiles from Italy

Abstract: PurposeDirect sales at the winery constitute one of the most used indicators for evaluating the success of a wine tourism experience. In this respect, service performance at the winery can have some influence on sales, which assumes that there is a direct link between the service level intensity of the wine tourism offer and the intensity level of direct sales at the winery; thus proposing that the global sustainability of the economic performance of the winery would increase if the wine tourism experience was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…This is an important consideration given that 37% of potential visitors rely on word-of-mouth recommendations when deciding which winery to visit (Bruwer and Reilly, 2006) and that the role of friends in influencing wine consumption is becoming more significant (Agnoli et al, 2013). Smyczek et al (2020) also emphasised the importance of a positive tastig room experience for the success of direct sales.…”
Section: Wine Tastings and Adoption Of Innovationmentioning
confidence: 99%
“…This is an important consideration given that 37% of potential visitors rely on word-of-mouth recommendations when deciding which winery to visit (Bruwer and Reilly, 2006) and that the role of friends in influencing wine consumption is becoming more significant (Agnoli et al, 2013). Smyczek et al (2020) also emphasised the importance of a positive tastig room experience for the success of direct sales.…”
Section: Wine Tastings and Adoption Of Innovationmentioning
confidence: 99%
“…Bruwer et al (2001) in a pioneering study concluded that even wine tourists with demographic similarities may express essential differences in other segmentation characteristics, such attitudes towards wine, product involvement and knowledge, lifestyles or wine consumption patterns and occasions. Subsequent authors claimed that psychographic segmentation variables can provide a complementary and more solid segmentation basis, by correlating wine consumption and wine tourism with characteristics like visitation motives, lifestyle, activities, personal values and skills (Thach and Olsen, 2004;Getz and Brown, 2006;Galloway et al, 2008;Liu et al, 2015;López-Guzmán, et al, 2016;Fotiadis and Williams, 2018;Smyczek et al, 2020). Corigliano (1996) developed four alternative segments centred on the lifestyles and attitudes of Italian wine tourists.…”
Section: Introductionmentioning
confidence: 99%
“…Key activities of the business model of wine-producing companies consist of production and sale of wine. Some companies expanded their basic business model by incorporating additional business activities, such as the sale of accessory goods and wine tourism activities [35]. They include wine tasting, restaurant and accommodation services, and events.…”
Section: Resultsmentioning
confidence: 99%